Sick building syndrome: do outdoor pollutants and pollen affect it? - González-Díaz, Sandra Nora; Hernández-Salcido, Grecia Jaqueline; de Lira-Quezada, Cindy Elizabeth; Cantú-Hernández, Jorge Alberto; Macouzet-Sánchez, Carlos; Macias-Weinmann, Alejandra; Acuña-Ortega, Natalhie (Frontiers in Allergy, 2024)
Introduction: Sick building syndrome (SBS) refers to non-specific complaints, including upper-respiratory irritative symptoms, headaches, fatigue, and rash, which are usually associated with a particular building by their temporal pattern of occurrence and clustering among inhabitants or colleagues. The aim of the study was to determine the association between the clinical manifestations of sick building syndrome with outdoor pollutants and airborne pollen.Methods: It was a descriptive and prospective observational study conducted from November 2021 to April 2022. It included subjects over 18 years old who completed an online survey on sick building syndrome (general symptoms, nasal, ocular, oropharyngeal, and skin symptoms) presented at home, housing information and personal history. The APS-330 from Pollen Sense ® was used to obtain data on pollen in the air and the local pollution monitoring system (SIMA) to obtain information regarding pollutants. For statistical analysis, SPSS version 16 was used.Results: A total of 402 surveys were included; 91% of the subjects reported having at least 1 symptom. Females presented more general symptoms (fatigue and headache) than males.Subjects with a personal history of atopy showed a higher prevalence of practically all symptoms. Airborne pollen exposure was positively associated with mucosal symptoms in eyes and nose. Outdoor fungi spore exposure was positively associated with oculo-nasal and cutaneous symptoms in the scalp.Conclusion: This study found significant associations with female gender and a history of atopy, which suggests a higher risk for these subjects. Despite the limitations of the study, we can conclude that there is an association between the clinical manifestations of sick building syndrome with indoor and outdoor pollution. Keywords: nasal symptoms, outdoor pollutants, pollen, rhinitis, sick building syndrome ✝ Results for "high amounts", taking the "non present" category as reference *p=<0.05 **p=<0.01 ***p=<0.001